Persepsi KPU Terhadap Caleg Perempuan - Siti Fatimah HSB; Syafri Gunawan; Khoiruddin Manahan Siregar (IAIN Padangsidimpuan, 2021)
This thesis is entitled the perception of the general election commission on the representation of women in the list of legislative candidates for the 2014-2019 period in the Mandailing Natal district (study of law number 7 of 2017 article 1 regarding elections. The general election commission has issued pkpu number 20 of 2018 regarding nominations for members of the DPR, the provincial dprd and district or city dprd and have been ratified by the ministry of law and human rights. But the birth of this pkpu did not go smoothly, especially regarding ex-corruptors not being allowed to nominate as members of the legislature. The involvement of women in politics from time to time continues to increase, one of the indicators is an increasing trend of women in the legislature, especially since the 1999 election until the 2009 election. However, in the 2014 election, women's representation has decreased and in law number 7 of 2017 concerning elections, it is necessary to have at least 30% of women's representation in the list of candidates to be legally registered. As a legislative candidate. This research is a type of qualitative research that emphasizes the analysis more on the inductive deductive inference process and on the analysis of the dynamics of the relationship between observed phenomena, using scientific logic. Qualitative research emphasizes efforts to answer research questions through a formal, argumentative way of thinking. This type of research is in the form of a field study. In this study the researcher found the results that the perception of the general election commission that the 30% quota of women's representation in legislative members in Mandailing Natal had not been fully implemented because of the individual factors of each woman and the lack of public trust in women due to negative views about gender